The reality of the use of artificial intelligence applications by students of the Faculty of Graduate Education at King Abdul-Aziz University in the light of some variables - Alfageeh, Halima Hasan; Alfarani, Leena Ahmad (Journal of Educational and Psychological Sciences, 2023)
The research aims to identify the reality of the use of artificial intelligence applications by students of the College of Education Graduate Studies at King Abdul-Aziz University in light of the variable of study stage and academic specialization. The research included (138) female students from the research community who were selected in a stratified random manner. The researcher used the descriptive analytical method to achieve the research objectives. It also relied on a questionnaire consisting of (28) sentences distributed over three axes to measure the reality of students' use of artificial intelligence applications, and after verifying their validity. And its stability, the research found that the degree of knowledge of the students of the Faculty of Educational Graduate Studies in the applications of artificial intelligence came with a degree of agreement (neutral), with arithmetic mean (2.96) and a percentage (59%), and the importance of using artificial intelligence applications with a degree of agreement (neutral) and an arithmetic average (3.18) and a percentage of (63.6%), while the obstacles to their use of artificial intelligence applications came with a degree of agreement (agree) and an arithmetic average (3.84), and a percentage of (76.8%), the research also found that there were no statistically significant differences at the significance level (≤ 0.05) in the responses of the research sample to all the axes of the questionnaire according to the variable of the study stage, while there were statistically significant differences at the significance level (≤ 0.05) in the responses of the research sample on the axes the study. A questionnaire according to the variable of academic specialization in favor of female students with specialization in educational techniques, and the researcher recommended the necessity of holding training courses to qualify postgraduate students to use artificial intelligence applications in the educational process and to provide adequate budget and equipment for that. Acquisition and use of artificial intelligence applications at the university.
Keywords: Artificial Intelligence applications; Postgraduate students; Reality of use